2023
DOI: 10.1111/hex.13904
|View full text |Cite
|
Sign up to set email alerts
|

Codesigning implementation strategies to improve evidence‐based stroke rehabilitation: A feasibility study

Elizabeth A. Lynch,
Lemma N. Bulto,
Maria West
et al.

Abstract: IntroductionPeople with lived experience are rarely involved in implementation science research. This study was designed to assess the feasibility of codesigning and delivering implementation strategies with people with lived experience of stroke and health professionals to improve evidence‐based stroke rehabilitation.MethodsWe used Experience‐Based CoDesign to design and deliver strategies to implement Stroke Clinical Guideline recommendations at one Australian inpatient stroke rehabilitation unit. Workgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In quantitative research, stakeholders play a key role in the design and dissemination of research findings, as demonstrated by studies conducted by Zhang and Morgan (40,42). Other studies also support the engagement of stakeholders in various stages of quantitative research, including selecting research topics and titles, formulating research questions, choosing appropriate measurement tools, designing interventions, and sharing research findings (40,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In quantitative research, stakeholders play a key role in the design and dissemination of research findings, as demonstrated by studies conducted by Zhang and Morgan (40,42). Other studies also support the engagement of stakeholders in various stages of quantitative research, including selecting research topics and titles, formulating research questions, choosing appropriate measurement tools, designing interventions, and sharing research findings (40,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 95%
“…Opposite to previous research in the field of SPSE, which primarily utilized quantitative and qualitative methodologies, only one mixed-methods study was identified. This study employed a co-design methodology (44).…”
Section: Discussionmentioning
confidence: 99%